The average Irish consumer a packaged food profile. Issue 11 (2nd November 2015) - Broderick, Meave; Bouchier-Hayes, Agnes; Larkin, Tracey; Griffith, ChristopherJ.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose It is the aim of this publication to provide a profile of the Average Irish Consumer (AIC) of preferences that drive food choice and purchasing of packaged foods. Design/methodology/approach A number of Irish consumer studies have been carried out and most notably by An Bord Bia. PERIscope (Purchasing and Eating in the Republic of Ireland) investigates Irish consumer food preferences from 2009 - 2013, based on data obtained from +1, 000 people in Ireland. Frequency analysis of these data sets was used to generate majority findings and preference attributes from which to propose a profile of the AIC. Component and cluster analysis was applied to investigate potential relationships between preference attributes and the significance of these relationships Findings The AIC is a female to whom price is a priority in food choice and prefers foods that are quick and easy to prepare. The AIC checks foods labels, looks for the low fat option, but has difficulty understanding nutrition claims and labels. The AIC buys local produce at least monthly, believes local food has less artificial/preservative ingredients and checks for the country of origin on food products. The AIC is conscious of environmental issues and prefers to buy from companies that are environmentally friendly. The AIC buys food in smaller packs as it means less waste, is possibly more convenient and lower priced. Originality/value It is the aim of this publication to provide a profile of the Average Irish Consumer (AIC) to assist food companies in understanding and targeting the consumers of their products when developing packaged food products.